A blueprint of changing nursing education globally - Editorial Office (AOSIS, 1996)
Education will play an essential role in building nursing's future. It is critical to the preparation of professionals as clinical nurses, managers, educators, and researchers all over the world, and ultimately in the improvement of the quality of care that nurses provide their patients\clients. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.